How disappointing: Startle modulation reveals conditional stimuli presented after pleasant unconditional stimuli acquire negative valence - Green, Luke J.S.; Luck, Camilla; Lipp, Ottmar (2020)
Past research on backward conditioning in evaluative and fear conditioning yielded inconsistent results in that self-report measures suggest that the conditional stimulus (CS) acquired the valence of the unconditional stimulus (US) in fear conditioning (assimilation effects), but the opposite valence in evaluative conditioning (contrast effects). Conversely, implicit measures of CS valence suggest assimilation effects in evaluative backward conditioning, whereas startle modulation indicates contrast effects in backward fear conditioning. The current study investigated whether US intensity could account for the dissociation on implicit measures between fear and evaluative conditioning. Self-report measures of evaluative learning indicated assimilation effects for forward conditioning, whereas backward contrast effects were observed with intense USs only. Blink startle modulation indicated assimilation effects in forward conditioning and contrast effects in backward conditioning, regardless of US intensity. Experiment 2 included a neutral US in order to assess whether the offset of the positive US elicits an opponent emotional response that mirrors relief (disappointment), which is thought to mediate the reduction in startle seen during backward CSs in fear conditioning. This opponent emotional response was evident as startle magnitude during backward CSs increased linearly with increasing US pleasantness. Omission of the forward CSs led to an assimilation effect in self-report measures. The current results extend our understanding of emotional learning to stimuli encountered after salient emotional events. Startle reflects the emotion prevailing after US offset, relief or disappointment, whereas self-report measures seem more attuned to factors such as US predictability and intensity.